Midwives’ experiences of pregnant women’s adherence to nutritional recommendations after bariatric surgery: a qualitative study - Anne Christenson (BMJ Nutrition, Prevention & Health)
Method We interviewed 17 midwives and analysed the text data with content analysis.Results The majority of midwives had treated women who were pregnant after bariatric surgery and who did not take sufficient vitamins and minerals and therefore were in a poor nutritional state. Many had met women who had become pregnant much earlier after surgery than recommended. Midwives often felt upset for the malnutrition risks for the baby, and sometimes blamed themselves for not providing enough nutritional support. Meanwhile, they found it easier to talk about weight with women who had undergone surgery than with other women with overweight or obesity.Conclusion These findings confirm the importance of prebariatric and postbariatric surgery support and information for young women regarding nutrition in relation to pregnancy. Preconception nutrition counselling with a dietician may be beneficial. Conversations about weight during pregnancy may be easier with women who have undergone bariatric surgery.